2020
DOI: 10.18632/aging.102954
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpressed ITGA2 contributes to paclitaxel resistance by ovarian cancer cells through the activation of the AKT/FoxO1 pathway

Abstract: Ovarian cancer is one of the most malignant tumors of the female reproductive system, with high invasiveness. The disease is a severe threat to women's health. The ITGA2 gene, which codes for integrin subunit α2, is involved in the proliferation, invasion, and metastasis of cancer cells. Although previous studies have shown that ITGA2 increases in ovarian cancer, the specific molecular mechanism of how ITGA2 promotes ovarian cancer proliferation and metastasis is still unclear. In this study, we confirmed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…In regards to ovarian cancer, a recent study demonstrated that ovarian cancer cells with elevated ITGA2 led to poor prognosis and survival. Overexpression of ITGA2 promoted in vitro cancer cell aggressiveness and in vivo tumor growth through regulation of the phosphorylation of forkhead box O1 (FoxO1) and AKT phosphorylation, which provided the mechanism for ITGA2-mediated paclitaxel-resistance in ovarian cancer ( Ma et al, 2020 ). However, it remains uncertain how ITGA2 regulates AKT/Foxo1 axis and how ITGA2 is regulated in the ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to ovarian cancer, a recent study demonstrated that ovarian cancer cells with elevated ITGA2 led to poor prognosis and survival. Overexpression of ITGA2 promoted in vitro cancer cell aggressiveness and in vivo tumor growth through regulation of the phosphorylation of forkhead box O1 (FoxO1) and AKT phosphorylation, which provided the mechanism for ITGA2-mediated paclitaxel-resistance in ovarian cancer ( Ma et al, 2020 ). However, it remains uncertain how ITGA2 regulates AKT/Foxo1 axis and how ITGA2 is regulated in the ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Integrins activate several signal transduction pathways, and aberrant expressions of integrins have been detected in several types of cancers; overexpression of integrins can enhance cancer cell development and progression [48][49][50][51]. ITGA2 forms a homodimer with ITGB1, and dysregulated levels of ITGA2/ITGB1 can mediate the signal pathways that enhance malignant transformation in multiple types of cancer cells [52][53][54][55]. In hepatocellular carcinoma cells, ITGA2 inhibits MST1 kinase phosphorylation and activates YAP pro-oncogenic activities [52].…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer cells, expressions of ITGA2 enhance AKT phosphorylation and further accelerate the phosphorylation of the oncogenic protein FOXO1. Moreover, a knockdown assay of ITGA2 has shown that sensitivity of paclitaxel is improved in paclitaxel-resistant ovarian cancer cells [54]. Furthermore, ITGA2 controls the MAPK pathways and EMT in gastric cancer cells, and these events closely contribute to the chemo-resistance of gastric cancer [55].…”
Section: Discussionmentioning
confidence: 99%
“…In this progress, non-coding RNAs is the most common molecular pathway that dually mediate or inhibit PTX resistance ( Datta et al, 2019 ; Yang et al, 2020 ). Integrin subunit α2 (ITGA2) is an oncogene factor which promotes metastasis and growth ability of cancer cells and it is thought to reduce sensitivity of cancer cells of PTX through activation of Akt/FoxO1 signaling pathway ( Ma et al, 2020 ; Qin et al, 2020 ). Furthermore, high mobility group box 1 (HMGB1) can activate c-Myc oncogene to induce PTX resistance ( Jung et al, 2020 ; Lei et al, 2020 ).…”
Section: Resistance In Taxanesmentioning
confidence: 99%